“I have never seen a thin person drink diet coke.” – analysis of insults in Donald Trump’s tweets @realdonaldtrump - Natri, Laura (My University, 2019)
The subject of this Master’s thesis deals with Donald Trump and the way he uses insults in his messages on the social media platform Twitter. His style of communication has attracted a lot of media attention and his tweets provide a very fertile ground for research. The data consists of 106 tweets collected from Trump’s personal Twitter account @realDonaldTrump. The tweets were chosen by a formula I created in order to gather congruent material that portrays the phenomenon in question and provide further insight to it. This study analyzes the tweets from a pragmatic perspective, combined with a critical perspective from Critical Discourse Analysis (CDA). The tweets were first categorized according to Searle’s (1969) approach known as Speech Act Theory (SAT) and the taxonomy of speech acts (SA). Cooperation, politeness and impoliteness are also important factors and it is discussed on the basis of Brown and Levinson (1987) and Grice’s (1975) conversational maxims and cooperative principle. In addition, the data was analyzed with Lecercle’s (1987) Anti-Gricean approach which focuses on the agonistic remarks in the way people communicate. The analysis revealed that a lot of the tweets go into the category of representatives, which as a category is characterized by speech acts that are stating, suggesting and describing and do not hedge the message, even when it is full of insults. Trump’s style of tweeting is very straightforward and on the basis of the analysis he seems not to be afraid of the possible outcome of his negative remarks on people. This is a statement of status; he does not have the need to hedge even the negative messages he uses to evoke reactions, and to eventually secure his place in the 2020 elections. Moreover, it can be argued that many of the insulting remarks can be explained either as tools of manipulation or as a matter of style that has been found effective in gaining a lot of media attention which hopefully then would translate into securing the favor of potential voters.
Keywords: critical discourse analysis, Donald Trump, political speech, speech act theory, cooperation principle, insults, social media